Preparation and Photocatalytic Properties of La Doped Bi2WO6 Nanomaterials - ZHANG Xiang-hui (Cailiao gongcheng, 2018)
La doped Bi2WO6 nanomaterials were synthesized by one step hydrothermal method using Bi(NO3)3·5H2O, Na2WO4·2H2O and La(NO3)3·6H2O as the raw materials. The phase composition and optical property of the as-prepared materials were systematically characterized by X-ray diffraction (XRD), UV-Vis diffuse reflectance spectroscopy and BET surface area. XRD result reveals that La is doped in Bi2WO6 successfully, and the prepared samples still possess orthorhombic structure. UV-Vis study shows the absorption edge of the prepared samples has a red-shift with the increase of La doping, indicating that La doping can broaden the absorbance range of the La doped Bi2WO6 materials. BET measurement shows that the specific surface area of La doped Bi2WO6 materials is increased with more La doping. In addition, the effect of La doping on the photocatalytic activities of the samples were measured by the degradation of methylene blue (MB). Results show that the best photocatalytic property is found in the 2.0% La doped Bi2WO6 nanomaterial; after 120min of reaction, the degradation rate of MB reaches 91%.